Enhancing CMRR in Fully Differential Amplifiers via Power Supply Bootstrapping - Spinelli, Enrique Mario (2025)
Fully differential amplifier circuits are well suited for instrumentation front ends and signal-conditioning applications. They offer high common-mode rejection ratios (CMRRs) regardless of the passive component tolerances but remain sensitive to imbalances in active devices. By using power supply bootstrapping (PSB), the CMRRs of these circuits can be improved, where they become independent of mismatches in both passive and active components. This technique works by forcing the power supply nodes to follow the common-mode input voltage, which significantly enhances the CMRR. However, this approach introduces stability issues that must be addressed through dedicated compensation strategies without degrading the overall performance. In this work, the theoretical background, a design methodology, and experimental validation are presented. The proposed technique was applied to a fully differential amplifier built with general purpose operational amplifiers. Prior to the PSB, the amplifier exhibited a CMRR of 90 dB at 1 kHz. A straightforward application of PSB led to instability in the common-mode behavior; however, with the proposed compensation method, the amplifier achieved stable operation and an improved CMRR of 130 dB.